Acupuncture 'dose' (Number of Treatments) and Insurance Benefits in the Usa. Issue 2 (April 2018) - Schwehr, Natalie A; Shippee, Nathan D; Johnson, Pamela Jo
Background: An adequate treatment dose, including a sufficient number of acupuncture treatments, is important for the clinical effectiveness of acupuncture treatment for common conditions. Objective: To examine the characteristics of US adults who used a full course of acupuncture (≥6 treatments), a short course (1–5 treatments) or no acupuncture, including use of insurance benefits for acupuncture among users. Methods: We used population-based survey data from the 2012 National Health Interview Survey (NHIS), the most current nationally representative data including use of acupuncture. We described subgroups of acupuncture users and used logistic regression to estimate the odds of past year acupuncture use versus non-use and completion of a full treatment course versus a short course. Covariates included demographic factors and health status. Analyses used strata, weights and clustering to account for the complex sample design. Results: Among acupuncture users, 38% completed a full course. Acupuncture use was low (1.5%), but odds were higher among women and those with greater education and less poverty. Those who used acupuncture insurance benefits and who had greater education were more likely to receive a full treatment course. Insurance benefits attenuated disparities in use by sex and race/ethnicity. Conclusion: Nationally, most people who use acupuncture do not receive a full treatment course. Considering evidence of effectiveness, low risk and relatively low cost of delivery, acupuncture could play a larger role in non-pharmaceutical treatment of common conditions such as pain. Policymakers should consider that, without insurance benefits for acupuncture, people are less likely to complete a full treatment course, which may contribute to disparities in use and health outcomes.